Analisis Faktor Penghambat Stuffing In pada Pemuatan Barang di Depo Petikemas PT. Sarana Bandar Nasional Surabaya - Langga, Feryan Mey; Sudirman; Setiono, Benny Agus (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2022)
This research entitled "Analysis of Stuffing In Inhibiting Factors for Smooth Loading of Goods at the Container Depot at PT. Sarana Bandar Nasional Surabaya. The purpose of this research is to find out the inhibition of stuffing in and the inhibition of the loading process on board and the efforts to improve PT. Sarana Bandar Nasional Surabaya. This research was conducted at PT. Surabaya National Airport Facilities. in May 2022. The research uses a qualitative descriptive approach, using observation, interview and documentation methods. From the results of the interview observation method, and the documentation shows that the stuffing-in inhibition is due to delays in starting work due to the customer/EMKL management coming late to the depot, natural factors due to rainy weather which can inhibit or delay stuffing-in activities, the stuffing-in block experiences crowds or density and less the area of the stacking yard thus hindering customers or other EMKL administrators from carrying out stuffing-in activities and the lack of available stock of available containers in the Stuffing In block, there are damaged containers and limited stock of available containers.